Peran Bapak dalam Pertumbuhan Rohani Anak Berdasarkan Efesus 6:4 dan Kolose 3:21 - Trivena Andrianikus (Voice, 2021)
The actions, examples, and attitudes of a child's life have the same tendencies as his parents. The basic principles of biblical teaching of parents' responsibilities to their children are specifically reviewed from the letters of the Apostle Paul in Ephesians 6:4 and Colossians 3:31. Children's spiritual growth is the role of the family. Children see and feel firsthand that, family is the closest environment that brings children to God. Genesis 2:20 writes that Eve was created by God as a helper for Adam. That is, the function of the wife is a helper from the husband. Paul's emphasis in Ephesians 6:4 and Colossians 3:21 clearly convey a father who carries out his function as the person responsible for the growth of the child, the wife as a helper. That is, in the family, the husband or father takes a major role in all conditions in the family. Whereas a wife or a mother helps her husband or father to carry out this responsibility.